Multiomics profiles of genome-wide alterations in H3K27ac in different lung lobes after acute graft-versus-host disease with MSCs treatment - Lu, Zixuan; Zhou, Yuming; Li, Chengyu; Abd El-Aty, A. M.; Liu, Chengxia; Luan, Xiying; Wang, Bin; Wang, Guoyan (Frontiers in Immunology, 2025)
The molecular characteristics of acute graft-versus-host disease (aGVHD) in different lung lobes and the treatment of aGVHD with mesenchymal stem cells are still poorly understood. In addition, despite the important role of acetylation on lysine 27 of histone H3 (H3K27ac) in the inflammatory response, little is known about genome-wide H3K27ac in GVHD and MSC treatment. In this study, we described 55 paired transcriptomes and genome-wide H3K27ac in five lung lobes, with groups designated as follows: control, GVHD, human placenta-derived MSC (hPMSC)-treated, and PBS-treated groups. We observed that inflammatory pathways were upregulated in GVHD but downregulated in hPMSCs. One algorithm was designed to identify the genes implicated in the prevention of GVHD by hPMSCs (the Rein02 gene), shedding light on a gene set with 892 Rein02 genes that are shared by all lobes and enriched in inflammatory pathways such as TNF-α signaling via NF-κb. The genome-wide H3K27ac data revealed lobe-specific patterns in the lobe behind the heart (H) and the left lobe (L) in the control and hPMSC groups, whereas these patterns were confused in the GVHD and PBS groups. Gene set enrichment analysis revealed that the hPMSC-induced variations in genome-wide H3K27ac were concentrated in the L and R3 lobes. The genes showing accordant tendencies (a-DEGs) between the transcriptome and H3K27ac highly overlapped between the a-DEGs and the Rein02 genes when hPMSCs were compared with GVHD. Integrated multiomics analysis suggested that the a-DEGs were predominantly expressed on myeloid (Fam174a, Ifi204, Slc7a11, Chil3, Capza2, Clec5a, and Clec4a2), T and NK cells (Eif3f, Cited2, Crybg1, Ndufs4, and Emb), B cells (Fam174a, Eif3f, and Blnk), and epithelial cells (Alcam, Chmp2b, and Metap2). The subset with high expression levels of these genes tended to present anti-inflammatory effects and reduced cytotoxic activity. Our study may provide new insights into the development of potential therapeutic drugs that target H3K27ac to assist in MSC treatment.